2003
DOI: 10.1088/0953-8984/15/19/332
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of NdxSrxMnO3(x  0.3, 0.5)

Abstract: We report on polarized Raman scattering of single crystals of Nd 1−x Sr x MnO 3 (x = 0.3, 0.5). Raman spectra of Nd 0.7 Sr 0.3 MnO 3 show a significant change through the metal-insulator transition. In the ferromagnetic metallic phase phonon modes grow in intensity and number while the electronic continuum becomes more pronounced. We suggest that these effects are due to the strong competition between the localization and the delocalization of carriers which is the origin of the largest colossal magnetoresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
8
20
0
Order By: Relevance
“…Recently, the polarized Raman spectra were recorded by Jandl et al [5] and they had assigned the observed frequencies to 10 Raman modes. It should be mentioned that Raman frequencies were also measured in case of Nd 0.7 Sr 0.3 MnO 3 by Choi et al [6]. In the present paper, an attempt has been made to study the zone center phonons in NdMnO 3 for the first time using a short range force constant model and then based on the atomic vibrations, the specific modes assigned in the experimental studies of Raman frequencies [5] were confirmed and for infrared frequencies assigned.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, the polarized Raman spectra were recorded by Jandl et al [5] and they had assigned the observed frequencies to 10 Raman modes. It should be mentioned that Raman frequencies were also measured in case of Nd 0.7 Sr 0.3 MnO 3 by Choi et al [6]. In the present paper, an attempt has been made to study the zone center phonons in NdMnO 3 for the first time using a short range force constant model and then based on the atomic vibrations, the specific modes assigned in the experimental studies of Raman frequencies [5] were confirmed and for infrared frequencies assigned.…”
Section: Introductionsupporting
confidence: 66%
“…One should note that each of the eigen vectors have three components, which makes The experimental values at 4.2 K obtained by Jandl et al [5] and Choi et al [6] for Nd 0.7 Sr 0.3 MnO 3 at 5 K are also shown. the table very lengthy and hence only the length of the total displacements are provided in the table.…”
Section: Resultsmentioning
confidence: 85%
“…The assignment of these modes is based on the lattice dynamic calculation [35] and similar to Choi et al [38]. The low-frequency mode at 210 cm −1 is attributed to the A 1g mode, which is the inphase rotation of the oxygen cage about the y-axis to adjacent MnO 6 octahedra.…”
Section: Resultsmentioning
confidence: 68%
“…The Pr 3+ ion has an ionic radius of 0.990 Å and Nd 3+ ion has an ionic radius of 0.983 Å, while the ionic radius of the Sr 2+ ion is 1.180 Å. Because the ionic radius of the Sr 2+ ion is larger than Pr 3+ or Nd 3+ ions, there is a limitation and substitution these ions for Sr in the structures (15) .…”
Section: Resultsmentioning
confidence: 99%